2001
DOI: 10.1038/sj.onc.1205009
|View full text |Cite
|
Sign up to set email alerts
|

Genome instability in secondary solid tumors developing after radiotherapy of bilateral retinoblastoma

Abstract: Genome alterations of seven secondary tumors (®ve osteosarcomas, one malignant peripheral sheath nerve tumor, one leiomyosarcoma) occurring in the ®eld of irradiation of patients treated for bilateral retinoblastoma have been studied. These patients were predisposed to develop radiation-induced tumors because of the presence of a germ line mutation in the retinoblastoma gene (RB1). Tumor cells were characterized by a high chromosome instability whereas microsatellites and minisatellites were found to be stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…Highdose radiation induces multiple double-strand breaks in chromosomes and breakage-fusion-bridge cycles, resulting in a gain of oncogenes, loss of tumor suppressor genes, and activation of DNA damage responses. 27 Telomerase expression can be activated during this process. 28 Therefore, ATRX loss and alternative lengthening of telomeres might not be needed for immortalization of radiation-associated tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Highdose radiation induces multiple double-strand breaks in chromosomes and breakage-fusion-bridge cycles, resulting in a gain of oncogenes, loss of tumor suppressor genes, and activation of DNA damage responses. 27 Telomerase expression can be activated during this process. 28 Therefore, ATRX loss and alternative lengthening of telomeres might not be needed for immortalization of radiation-associated tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is evidence of genetic instability in radiogenic tumours, it may not be possible to distinguish between instability that may be a consequence of malignant changes in cells and instability that might reflect the delayed effects of exposure to ionizing radiation, that is, is such instability a cause or a consequence of malignancy. However, it has been suggested that instability-generated p53 point mutations are important in the genesis of thorotrastinduced tumours (Iwamoto et al, 1999;Ishikawa et al, 2001) and that the high level of genome instability in secondary solid tumours developing after radiotherapy of bilateral retinoblastoma, including uncommon p53 mutations, is attributable to instability rather than a direct effect of ionizing radiation (Lefevre et al, 2001). Clearly, any process that increases the frequency with which genetic changes arise will increase the probability of relevant genetic changes in potential target cells and the correlation between the genotype-dependent expression of chromosomal instability in mouse mammary epithelial and susceptibility to mammary tumours supports a role for radiation-induced instability in the process of tumorigenesis (Ponnaiya et al, 1997;Ullrich and Ponnaiya, 1998).…”
Section: The Response To Damaging Signalsmentioning
confidence: 99%
“…Several studies were performed on sarcomas that developed within tissue irradiated for a previous malignancy and were diagnosed many years after treatment ( Table 2). Most of the sarcomas occurred after varying types of first tumors, except for one study among patients treated for retinoblastoma (Lefevre et al, 2001). Among the second tumor studies that Shoshan, 2000 (Lefevre et al, 2001).…”
Section: Tumor Tissue Analysis Of Second Primary Cancersmentioning
confidence: 99%
“…Most of the sarcomas occurred after varying types of first tumors, except for one study among patients treated for retinoblastoma (Lefevre et al, 2001). Among the second tumor studies that Shoshan, 2000 (Lefevre et al, 2001). In the study by Gafanovich et al (1999), all the tumors showed evidence of MIN.…”
Section: Tumor Tissue Analysis Of Second Primary Cancersmentioning
confidence: 99%
See 1 more Smart Citation